The coastal «retamal» around the Guadiana river - Pérez Chiscano, José Luis (Lazaroa, 1983)
The situation, flower composition and the syntaxonomy of the Retama monosperma (L.) Boiss. population in spanish-portuguese coast around of the Guadiana river are described.